An improved approach for the continuous retardation spectra of concrete creep and applications - Zhou, Xinzhu; Bai, Linhong; Rong, Hua; Fan, Xinglang; Zheng, Jianjun; Geng, Yan (Frontiers in Materials, 2024)
Creep is an important physical property of concrete and could lead to additional displacements, stress redistribution, and even cracking in concrete structures, inducing prestress losses of large-scale prestressed concrete structures. When the exponential algorithm is used to calculate the long-term creep of concrete, it is usually necessary to apply the continuous retardation spectra of the material. In the improved approach proposed in this paper, the continuous retardation spectra can be obtained by the Weeks inverse Laplace transform. The CEB MC90 creep model is taken as an example to analyze the computational process, efficiency, and error of the approach. The improved approach is further applied to the ACI 209R-92, the JSCE, and the GL2000 concrete creep models. Through comparison with the other methods, the advantages of the improved approach are illustrated and some useful conclusions are finally drawn.1 2To describe viscoelastic materials, their constitutive properties can be represented by the Kelvin chain model. In the Kelvin chain model, the deformation of a material can be characterized by a number of Kelvin units and an additional spring unit assembled in series, as shown in Figure 1. Each Kelvin unit is composed of a spring and a dashpot assembled in parallel. All these units bear the same stress, and the total strain 𝜀 is equal to the sum of the deformations of each Kelvin unit and the spring unit.